Meta-Analysis: Application of Theory of Planned Behavior on Acupuncture Therapy Utilization in Cancer Patients with Pain - Fatimah Rahmawati; Argyo Demartoto; Hanung Prasetya (Indonesian Journal of Medicine, 2023)
Background: Cancer is a health disorder caused by the formation of abnormal cells that grow past the normal cell cycle limit and can attack and spread to other parts of the body. In the Theory of Planned Behavior, one's behavior can be influenced by three main aspects, including attitudes, subjective norms, and behavioral control. The purpose of this study was to estimate perceived benefits, perceived barriers, and subjective norms regarding the use of acupuncture therapy in cancer patients with pain. Subjects and Method: This was a systematic review and meta-analysis. This study uses the PICO model. The meta-analytic study was carried out by searching for articles from databases in electronic form using Google schoolar, PubMed, and Elsevier. Article searches were conducted from 05 February to 10 March 2023. The keywords used were “Theory of Planned Behavior” OR “TPB” AND “Acupuncture” OR “Complemantary Alternative Medicine” AND “Cancer” OR “Pain” AND “Cancer Pain” OR “Cross-Sectional”. The inclusion criteria for this study were complete articles using cross-sectional research, published years from 2007-2022. Analysis of the articles in this study used RevMan 5.3 software. Results: 8 cross sectional studies from North United States and Asia (Korea and Malaysia) were selected for meta-analysis. High perceived benefit (aOR= 1.20; 95% CI= 1.09 to 1.33; p<0.001) and strong subjective norm (aOR= 1.05; 95% CI= 1.01 to 1.08; p= 0.005) increased acupuncture utilization to reduce pain. High perceived barrier reduced acupuncture utilization (aOR= 0.94; 95% CI= 0.91 to 0.97; p < 0.001). Conclusion: High perceived benefit and strong subjective norm increase the use of acupuncture. Strong perceived barrier reduces the use of acupuncture. Keywords: Theory of Planned Behavior, cancer patients with pain, acupuncture therapy